2015
DOI: 10.1016/j.molp.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in the Enzymatic Activities of a Tomato and Solanum pennellii Alcohol Acyltransferase Impacts Fruit Volatile Ester Composition

Abstract: Tomato fruits accumulate a diverse set of volatiles including multiple esters. The content of ester volatiles is relatively low in tomato fruits (Solanum lycopersicum) and far more abundant in the closely related species Solanum pennellii. There are also qualitative variations in ester content between the two species. We have previously shown that high expression of a non-specific esterase is critical for the low overall ester content of S. lycopersicum fruit relative to S. pennellii fruit. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 47 publications
0
69
0
Order By: Relevance
“…As Figure 7B shows, a significant induction of TomloxF was detected upon bacterial infection with both strains at all the studied time points, and this induction was greater when ETI had been established. Regarding alcohol acyltransferases, five AAT genes (SlAAT1 - 5) have been identified in tomato (Goulet et al, 2015). We observed that the induction of AAT1 followed a similar pattern to that of TomloxF ( Figure 7C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Figure 7B shows, a significant induction of TomloxF was detected upon bacterial infection with both strains at all the studied time points, and this induction was greater when ETI had been established. Regarding alcohol acyltransferases, five AAT genes (SlAAT1 - 5) have been identified in tomato (Goulet et al, 2015). We observed that the induction of AAT1 followed a similar pattern to that of TomloxF ( Figure 7C ).…”
Section: Resultsmentioning
confidence: 99%
“…In tomato plants, ( Z )-3-hexenol, ( Z )-3-hexenal, and ( Z )-3-hexenyl acetate are the dominant LOX products in the volatile emission after Botrytis cinerea inoculation (Jansen et al, 2009). Volatile esters not only contribute to the aroma of many fruits and flowers, but are also related to plant defense and plant-to-plant signaling (Goulet et al, 2015). The ester ( Z )-3-hexenyl acetate is one of the most abundant volatiles to be emitted from mechanically or herbivore-damaged Arabidopsis thaliana plants (D’Auria et al, 2007), and can prime a defense response in nearby plants (Engelberth et al, 2004; Frost et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Research has led to the characterization of several genes involved in the biosynthesis of fatty acid-derived volatiles (Speirs et al , 1998; Chen et al , 2004; Matsui et al , 2000, 2007; Shen et al , 2014), apocarotenoids (Simkin et al , 2004), esters (Goulet et al , 2012, 2015), phenylpropanoids (Tieman et al , 2010; Mageroy et al , 2012), and other phenylalanine-derived volatile compounds (Tieman et al , 2006 a , 2007), and the role of conjugation in the accumulation and emission of volatiles (Louveau et al , 2011; Tikunov et al , 2013). However, we have only obtained partial knowledge of the metabolic pathways and the genes involved in volatile biosynthesis and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Similar glycosylation/glycosidation mechanisms operate in grape varieties that usually accumulate large amounts of volatile precursors as conjugated compounds that are released following tissue maceration (Rambla et al, 2016, 2017b). Using target approaches based on knowledge of metabolic pathways has led to the characterization of several genes involved in the biosynthesis of phenylpropanoids (Tieman et al, 2010; Mageroy et al, 2012), fatty acid-derived volatiles (Speirs et al, 1998; Chen et al, 2004; Matsui et al, 2007; Shen et al, 2014), apocarotenoids (Simkin et al, 2004), esters (Goulet et al, 2015), and other phenylalanine-derived volatile compounds (Tieman et al, 2010), and in the conjugation and/or deconjugation and emission of volatiles (Tikunov et al, 2013). Moreover, Schauer et al (2005) performed one of the first GC–MS-based surveys of the relative metabolic levels of leaves and fruits of S. lycopersicum and five sexually-compatible wild tomato species ( S. pimpinellifolium, S. neorickii, S. chmielewskii, S. habrochaites , and S. pennellii ).…”
Section: The Contributions Of Biotechnological Tools To Link Genomic mentioning
confidence: 99%